Progressive Education in Ahmad Dahlan's Perspective: Schools and Madrasahs as Agents of Social Change - Aisyatur Ridlo Al Baidlo’; Muhammad Farih Alfaaza; Abd. Rachman Assegaf (IQRO: Journal of Islamic Education, 2026)
This study examines the essence of Ahmad Dahlan’s progressive education, the role of schools and madrasahs as progressive educational institutions, and their transformation into agents of social change. Using a qualitative library research design with character studies, data were collected from Ahmad Dahlan’s writings, Muhammadiyah documents, books, and relevant scholarly articles, and analyzed through content, historical, and philosophical approaches. The findings show that Ahmad Dahlan’s progressive education is founded on the trilogy of intelligence, experience, and progress, which is reflected in four core principles: knowledge integration, contextualization, balance, and progressiveness. These principles transform schools and madrasahs into agents of social change through Al-Ma’un theology, prophetic leadership, and sustainable community empowerment. The study proposes a conceptual model of transformative schools and madrasahs by integrating Ahmad Dahlan’s educational philosophy with social change theory. The findings provide practical implications for strengthening educational policies and institutional practices that promote socially responsible and transformative education. However, this study is limited to conceptual and literature-based analysis; therefore, future research should empirically validate the proposed model across diverse educational contexts.